Analisis Keterlambatan Pengiriman Barang Sampai Ke Konsumen di Kantor Pos Bandar Lampung Menggunakan Metode Fishbone - Talitha Nirmala Ramadhani (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Pos Indonesia is an Indonesian State-Owned Enterprise (BUMN) engaged in postal services. Now, the form of Pos Indonesia's business entity is a Limited Liability Company and is often referred to as PT. Indonesian post. The form of the Pos Indonesia business is according to Government Regulation of the Republic of Indonesia Number 5 of 1995. This Government Regulation contains the transfer of the initial form of Pos Indonesia from a public company (perum) to a state-owned company. The services provided by the post are on a national and international scale. In carrying out the postal processing and distribution system, it is guided by the CPTDR principle, namely: Collecting, Processing, Transporting, Delivering and Reporting. This study aims to find out what are the causes of delays in delivery to consumers. Data collection is done by interview. Meanwhile, the method used is the fishbone method, which is a common tool used to help organizations solve problems by conducting a cause and effect analysis of a situation in a diagram such as a fishbone. In the fishbone diagram there are five parts that result in delays in the delivery of goods, namely from Man, Material, Method, Environment, Machine.